Some botanical characteristics of green foxtail (Setaria viridis) and harvesting experiments on the grass - Lu, Tracey L.-D. (Antiquity, 1998)
Green foxtail (Setaria viridis) is an annual grass widely distributed over the Old World, including China, where evidence of the earliest foxtail millet domestication to date has been discovered in the Cishan assemblage, Hebei province, dated to approximately 7900–7500 BP (Institute of Archaeology CASS 1991). Isozymic analysis and interspecific cross between S. viridis and S. italica (domesticated foxtail millet) demonstrated that S. viridis is the progenitor of domesticated foxtail millet (Gao & Chen 1988; Li et al. 1945). Yet little is known about the process of millet domestication, and even less about either the botanical characteristics of S. viridis or its cultural significance regarding human domestication.